1997
DOI: 10.1161/01.hyp.29.1.506
|View full text |Cite
|
Sign up to set email alerts
|

Role of Substance P in Blood Pressure Regulation in Salt-Dependent Experimental Hypertension

Abstract: The partlclpatlon of substance Pm the pathogenesls of five models of expenmental hypertension, le, DOCA-salt, subtotal nephrectomy, one-kidney-one chp renovascular, two-kldney-one clip renovascular, and spontaneous hypertension, was evaluated via an acute infusion of a newly synthesized potent, specific nonpeptlde antagonist of substance P at the NK-1 receptor, the agent CP 96,345 In conscious unrestrained rats, CP 96,345 induced significant and sustained increases m mean arterial pressure of DOCA-salt, subtot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
3
16
0
Order By: Relevance
“…This is unlikely as in our previous studies on DOC-salt hypertension, control animals that underwent uninephrectomy did not exhibit a pressor response on intravenous administration of span-II. 15 The results presented herein are consistent with the findings of Kohlmann et al, 10 who showed that acute inhibition of the NK-1 receptor with a non-peptide SP antagonist increased the MAP in 3 salt-dependent models, DOC-salt, SN-salt, and 1-kidney-1 clip, but failed to do so in genetic and saltindependent models such as the spontaneously hypertensive rats (SHR) and the 2-kidney-1 clip model. We have since extended these results to the DOC-salt model of hypertension, in which the neuronal expression and release of SP is increased as a compensatory mechanism to the elevated BP, 15 and in the DAHL-salt model (a genetic and salt-independent model of hypertension), in which SP does not seem to play a compensatory vasodilator role.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is unlikely as in our previous studies on DOC-salt hypertension, control animals that underwent uninephrectomy did not exhibit a pressor response on intravenous administration of span-II. 15 The results presented herein are consistent with the findings of Kohlmann et al, 10 who showed that acute inhibition of the NK-1 receptor with a non-peptide SP antagonist increased the MAP in 3 salt-dependent models, DOC-salt, SN-salt, and 1-kidney-1 clip, but failed to do so in genetic and saltindependent models such as the spontaneously hypertensive rats (SHR) and the 2-kidney-1 clip model. We have since extended these results to the DOC-salt model of hypertension, in which the neuronal expression and release of SP is increased as a compensatory mechanism to the elevated BP, 15 and in the DAHL-salt model (a genetic and salt-independent model of hypertension), in which SP does not seem to play a compensatory vasodilator role.…”
Section: Discussionsupporting
confidence: 89%
“…7,8 Whereas in DOC-salt hypertension the antihypertensive activity of CGRP is mediated through an increase in neuronal expression and peptide release, in SN-salt hypertension this antihypertensive activity is mediated via enhanced sensitivity of the vasculature to the vasodilator activity of this peptide. 9 Likewise, Kohlmann et al 10 reported that endogenous SP acts to attenuate the blood pressure (BP) increase in 3 rat models of salt-dependent hypertension, including the SN-salt model. However, the status of SP expression, peptide release, as well as the mechanism of its counterregulatory role has not been determined in this setting.…”
mentioning
confidence: 99%
“…2B). The MAP began to rise 30 s after administration and was elevated for ϳ180 s similar to CGRP 8 -37. Spantide II is a peptide that is also rapidly degraded in the circulation (33). No significant changes in heart rate were observed with either antagonist.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies (3,11,14,20,32,33,45,50,51,53) the participation of these sensory neuropeptides in the regulation of systemic BP has been observed primarily in rodent models of experimental hypertension. In these studies our laboratory and others have reported that CGRP and/or SP play a compensatory vasodilator role in pulmonary hypertension (3,11,32,53); DOC salt (30,50); SN salt (51); two-kidney, one-clip (14); and L-NAME-induced hypertension during pregnancy (20).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation